Kesan Parakuat Terhadap Kadar Fotosintesis Daun Jacquemcmtia paniculata - Siais, Salehan; Song, Wong Lai; Awang, Mohammad (1992)
The rate of photosynthesis of Jacquemontia paniculata leaves and the effect of different concentrations of paraquat solutions on the rate of photosynthesis were studied using the oxygen-electrode Clark-type. The mean value of the photosynthetic rate of Jacquemontia paniculata leaves at room temperature was found to be 60.24 ± 4.20 Ilmol O/dm2/hour. The optimum concentration ofparaquat solution to be used as a sprayed herbicide for Jacquemontia paniculata leaves is 0.0054 M.